Effects of Long-Term Treatment with Ranirestat, a Potent Aldose Reductase Inhibitor, on Diabetic Cataract and Neuropathy in Spontaneously Diabetic Torii Rats. (13th March 2013) - Ota, Ayumi; Kakehashi, Akihiro; Toyoda, Fumihiko; Kinoshita, Nozomi; Shinmura, Machiko; Takano, Hiroko; Obata, Hiroto; Matsumoto, Takafumi; Tsuji, Junichi; Dobashi, Yoh; Fujimoto, Wilfred Y.; Kawakami, Masanobu; et al.
Abstract : We evaluated ranirestat, an aldose reductase inhibitor, in diabetic cataract and neuropathy (DN) in spontaneously diabetic Torii (SDT) rats compared with epalrestat, the positive control. Animals were divided into groups and treated once daily with oral ranirestat (0.1, 1.0, 10 mg/kg) or epalrestat (100 mg/kg) for 40 weeks, normal Sprague-Dawley rats, and untreated SDT rats. Lens opacification was scored from 0 (normal) to 3 (mature cataract). The combined scores (0–6) from both lenses represented the total for each animal. DN was assessed by measuring the motor nerve conduction velocity (MNCV) in the sciatic nerve. Sorbitol and fructose levels were measured in the lens and sciatic nerve 40 weeks after diabetes onset. Cataracts developed more in untreated rats than normal rats (P < 0.01 ). Ranirestat significantly (P < 0.01 ) inhibited rapid cataract development; epalrestat did not. Ranirestat significantly reversed the MNCV decrease (40.7 ± 0.6 m/s) in SDT rats dose-dependently (P < 0.01 ). Epalrestat also reversed the prevented MNCV decrease (P < 0.05 ). Sorbitol levels in the sciatic nerve increased significantly in SDT rats (2.05 ± 0.10 nmol/g), which ranirestat significantly suppressed dose-dependently, (P < 0.05, <0.01, and <0.01); epalrestat did not. Ranirestat prevents DN and cataract; epalrestat prevents DN only.